Pengaruh Work From Home Terhadap Work Life Balance Pada Perempuan Bekerja Di Kota Mataram Di Masa Pandemi Covid-19 - Siti Nurmayanti; Dwi Putra Buana Sakti; Baiq Handayani Rinuastuti (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This study aims to analyze the effect of work from home on work life balance for women working in Mataram City during the COVID-19 pandemic. The paradigm used in this research is the positivist paradigm with quantitative methods as the right design to achieve the research objectives. Through this approach, the researcher distributed a structured questionnaire aimed at obtaining data to be analyzed to 84 female respondents who worked with the criteria of being married, living with a partner, having at least 1 child and having done WFH. The data were analyzed using simple linear regression. The results showed that work from home had an effect on the work life balance of working women in the city of Mataram